RELIGION AND GENOCIDE - Jacobs, Steven L., 1947- ([S.l.])
1 online resource
Keywords: Religion and Genocide: Changing the Conversation is a cutting-edge introduction to the complex and controversial relationship between religion and genocide. This book aims to widen the reader's understanding of religion and those who practice it, the nexus of religion and violence, and those who legitimate their violence by framing it in religious terms by looking at notions of holy wars, religious wars, and genocide and the practitioners of such. This book delves into our current thinking of ourselves as biological entities, our relationship to genocide, and the impact of geography (including climate change) and diseases on our humanity and our ability to commit genocide. Tying together all these seemingly disparate threads, this text concludes with the significant and still largely unanswered question: "Where do we go from here?". Highlighting the complex relationship between religion and genocide, this is an essential read for students and academics studying religion and violence, Judaism, Judaic studies, and holocaust and genocide studies. Religion and Genocide will also be of interest to researchers in related subjects such as history, politics, sociology, and anthropology.